If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 5) = 0 Reorder the terms: -3(5 + x) = 0 (5 * -3 + x * -3) = 0 (-15 + -3x) = 0 Solving -15 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -3x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -3x = 0 + 15 -3x = 0 + 15 Combine like terms: 0 + 15 = 15 -3x = 15 Divide each side by '-3'. x = -5 Simplifying x = -5
| 0.99=10+.89 | | 0.5x+3.2=3.7 | | 98=15+x | | 3(a+2b-2)-2(2a-5b-1)= | | 8x(2+5)-4=68 | | 10k+7-3-11= | | 4x-5-2x/5=3/5 | | X-8+10=14 | | 3m^2=21m | | 38+7k=8(k+1) | | 1(7x+2x)= | | n/0.8=0.05/4 | | 13y-56=105 | | 4x+2=8y-22 | | -6x-x=2x | | 36xy=14.76 | | 5(2n-8)-4n=7n-39 | | 4x(7*8)=54 | | b-1/15=3/5 | | 4x+y-z=4 | | h(t)=-16t^2+24t+7 | | 6(4y+8)=6y | | 4p+3=9 | | (6m^-2n/mn^-1)^3 | | X-8+10= | | (4x-5)+x=16 | | 2x^5-3x^3+8x^2=0 | | 3m-51=12 | | 14+2v=1+5v-8 | | 20x-10forx=4 | | b-1=3/5*15 | | (3x^4/x^-5)^-2 |